If T is the midpoint, then, it is necessary that ST = TU. Use the given expressions for ST and TU:
ST = 9x
TU = 6x + 30
equal the previous expressions and solve for x, as follow:
ST = TU
9x = 6x + 30 subtract 6x both sides
9x - 6x = 30 simplify left side
3x = 30 divide by 3 both sides
x = 30/3
x = 10
next, replace the value of x into the expressions for ST and TU:
ST = 9x = 9(10) = 90
TU = 6x + 30 = 6(10) + 30 = 60 + 30 = 90
and the value of SU is:
SU = ST + TU = 90 + 90 = 180
Then, you have:
ST = 90, TU = 90, SU = 180